65.9k views
4 votes
How do you solve 6-9(4p-3)= 2(6p+7)+3

2 Answers

2 votes
Answer: I got p=1/3

Explanation: Different easier way.

6-9*(4*p-3)-(2*(6*p+7)+3)=0

(6-(9•(4p-3)))-(2•(6p+7)+3) = 0

(6 - 9 • (4p - 3)) - (12p + 17) = 0

16 - 48p = -16 • (3p - 1)

-16 • (3p - 1) = 0

-16 = 0

3p-1 = 0

3p = 1

p = 1/3 = 0.333
User Msonowal
by
6.2k points
4 votes

Answer:

p= 1/3

​ =0.333

Explanation:

Simplifying

6 + -9(4p + -3) = 2(6p + 7) + 3

Reorder the terms:

6 + -9(-3 + 4p) = 2(6p + 7) + 3

6 + (-3 * -9 + 4p * -9) = 2(6p + 7) + 3

6 + (27 + -36p) = 2(6p + 7) + 3

Combine like terms: 6 + 27 = 33

33 + -36p = 2(6p + 7) + 3

Reorder the terms:

33 + -36p = 2(7 + 6p) + 3

33 + -36p = (7 * 2 + 6p * 2) + 3

33 + -36p = (14 + 12p) + 3

Reorder the terms:

33 + -36p = 14 + 3 + 12p

Combine like terms: 14 + 3 = 17

33 + -36p = 17 + 12p

Solving

33 + -36p = 17 + 12p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-12p' to each side of the equation.

33 + -36p + -12p = 17 + 12p + -12p

Combine like terms: -36p + -12p = -48p

33 + -48p = 17 + 12p + -12p

Combine like terms: 12p + -12p = 0

33 + -48p = 17 + 0

33 + -48p = 17

Add '-33' to each side of the equation.

33 + -33 + -48p = 17 + -33

Combine like terms: 33 + -33 = 0

0 + -48p = 17 + -33

-48p = 17 + -33

Combine like terms: 17 + -33 = -16

-48p = -16

Divide each side by '-48'.

p = 0.3333333333

Simplifying

p = 0.3333333333

User Yakup
by
6.5k points